NILAI KEARIFAN LOKAL DALAM TUNJUK AJAR MELAYU KARYA TENAS EFFENDI - Marlina, Marlina (Diksi, 2020)
(Title: The Value of Local Wisdom in "Tunjuk Ajar Melayu" by Tenas Effendi).This study aims at determining the value of local wisdom contained in the Tunjuk Ajar Melayu (Malay Guidance of Life) by Tenas Effendi. The main problem is what the values of local wisdom contained in the Tunjuk Ajar Melayu are. This study applied descriptive qualitative method. The primary data source is the Tunjuk Ajar Melayu contained in the book "Kesantunan dan Semangat Melayu (Politeness and Spirit of Malay)" by Tenas Effendi. The result of the research shows that Tunjuk Ajar Melayu contained local wisdom values which had to be maintained and preserved by the community owners. These values are having good intentions and good character, setting oneself in the harmonious position, positioning oneself smartly in certain situation and condition, being wise in considering and tolerating, willing to sacrifice and willing to yield, having humble heart, and maintaining good relations with neighbors. One way to maintain and preserve the values of local wisdom is to include the material of the Tunjuk Ajar Melayu as one of the local content of teaching materials in schools in Riau.Keywords: Malay guidance of life, values, local wisdom